Investment Opportunity Set of Telecommunication Companies Reviewed from Financial Performance Aspects - Eka Handriani; Indraah Kolandaisamy; Dongmei Cao; Tomonori Sumi; Nahayo Alphonse; Seyed Jalal Sadeghi Sharif (Tinta Emas Publisher, 2025)
The telecommunications industry in Indonesia has a strategic role in supporting economic development, especially in supporting economic activities between regions. This study aims to analyze the effect of Return on Asset (ROA), Debt to Equity Ratio (DER), and Sales Growth on Investment Opportunity Set (IOS) in telecommunications companies listed on the Indonesia Stock Exchange (IDX) for the period 2015-2020. This study uses a quantitative method with secondary data obtained from the companies financial statements through the official IDX website. Data analysis was carried out using multiple linear regression with the help of SPSS software. The results of the study show that ROA and DER have a significant effect on IOS, while Sales Growth does not have a significant effect partially. Simultaneously, the variables ROA, DER, and Sales Growth have a significant effect on IOS. This study provides implications that the companies financial performance, especially in increasing ROA and managing DER, can increase investment opportunities. Further studies are expected to expand the research variables by using intervening variables for a more comprehensive understanding.